Retrospective Study On Management Of Gestational Trophoplastic Disease In Baghdad Teaching Hospital - Al-Baldawi, Riyadh A. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: The Aim Of This Study Is To Determine The Modalities Of Treatment Of GTD In Baghdad Teaching Hospital And To Assess The Efficacy Of Our Management Protocols.Patients &Methods: Department Of Obstetrics & Gynecology- Baghdad Teaching Hospital. Retrospective Analysis Of Case Records Between January 1999 To December2000. 41 Patients' Data Were Reviewed For Age, Gravidity, Parity, Blood Group, Antecedent Pregnancy And Clinical Presentation At The Time Of Diagnosis. Monitoring Of Hcg Level Before And After Chemotherapy, Other Investigations Were Reviewed, Looking For Number, Size And Site Of Metastasis. The Patient Were Classified According To WHO Scoring System. We Evaluate The Lines )f Management, Chemotherapeutic Protocols And The Number Of Chemotherapy Courses For 'atient's Remission. Results; The Most Common Presenting Symptom Was Vaginal Bleeding 70.7%. Dilatation And iuction Curettage Was The First Line Of Treatment, Although 4 Patients (9.8%) Ended With hysterectomy For Persistent Bleeding. Based On WHO Scoring System, Initial Assessment Shows That 78.04 % In The Low Risk Group, And 19.5 %In The Medium Risk Group And One Patient In The High Risk Group. Complete Remission Was Achieved With Administration Of 2- 7 Courses Of Single Agent Chemotherapy In 84.3 % In The Low Risk Group, While 5 Patient (15.6%) Show Resistance To Single Agent Protocol And Shifted To Combined Chemotherapy. Nine Patients In The Medium And High Risk Groups Started With Combined Chemotherapy. The Cure Rate In The Low And Medium Risk Groups Were 100%.Conclusion; Chemotherapy Is The Main Line Of Management For Persistent GTD In Baghdad Teaching Hospital, And For The Low Risk Group We Found That Parantral MTX And Folinic Acid Had A Very Good Remission Rate And Patients Whom Developed Resistance , And Those In The Medium Risk Group Can Achieve Excellent Remission Rate With Multiple Agents Chemotherapy.